Variants in the Chromosomal Region of the Myostatin Gene and Their Association With Lines, Performance, and Body Measurements of Quarter Horses - de Matteis, Rafael [UNESP]; Pereira, Guilherme L. [UNESP]; Casarotto, Letícia T. [UNESP]; Tavernaro, Anna Júlia S. [UNESP]; Silva, Josineudson Augusto II. V. [UNESP]; Chardulo, Luís Artur L. [UNESP]; Curi, Rogério A. [UNESP] (Elsevier, 2018)
The objectives of this study were to evaluate differences between the racing and cutting lines of Quarter Horses in the allele frequencies of polymorphisms identified in the chromosomal region of the myostatin gene (MSTN, ECA18) and to analyze the association of polymorphisms in this chromosomal region with the estimated breeding values (EBVs) for racing performance, given by the maximum speed index, height at withers (HW), thoracic perimeter (TP), and body length (BL) in the racing line, and with EBVs for HW, TP, and BL in the cutting line. Genomic, phenotypic, and pedigree data from 420 horses of both sexes, registered in the Brazilian Association of Quarter Horse breeders, were used (352 of racing line and 68 of cutting line). In the genome region studied (MSTN ± 2 Mb), 46 SNPs and one SINE (ERE1) shared among the cutting and racing lines were identified, and the allele frequencies of 32 SNPs and the one SINE differed significantly between the two lines (P <.05). Furthermore, the part of this region closest to the MSTN (±1 Mb) was found to be less polymorphic in the racing line. Regarding phenotype-associated polymorphisms (unadjusted P <.05), those related to HW in the racing line are highlighted because of their large number and extensive linkage disequilibrium. In addition, these markers exhibited significantly higher frequencies of the favorable allele compared to the cutting line.
Keywords: ERE1; Horse; Molecular markers; QTL; SNP; Speed